PEDAGOGICAL PROCESS FACILITATING PHYSICAL ACTIVITY OF PRE-SCHOOLERS - Stangaine, Inga; Augstkalne, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The research covers analysis of theoretical literature on significance of physical activities in the development of child’s integrity, as it is a well-known fact that child is researcher and his/her activity is manifested through movement. Child gets his first impressions about surrounding world through movement – the more diverse motions are, the more information is acquired, and the more intense is intellectual development thereof. However, quite often pedagogical process does not consider the specific factors facilitating capacity of child’s physical, functional, motion and mental development.To conduct the research, an aim was set to study physical activity of children in pre-school and opportunities to increase it via pedagogical process.The research was carried out by using suitable research methods: analysis of theoretical literature, observations, and pedometrics.The research covers analysis of physical activity of children and amount thereof during a day in pre-school, as well as is aimed at seeking solutions to improve it.Within the research, it was concluded that pre-school education institutions do no provide children with sufficient physical activity, as 75 % of the children do not make the needed number of steps during a day in pre-school.In relation to the competence-based educational content, the research gives suggestions for facilitation of physical activity of children in pedagogical process.